(3EOGQI GdLhOI aj GdefXeGJ GdeJejRIs - (3NVjQ cGXe(B, (3MehOs; (3QhGf efjQ GdTjN(B, s ((3YeGf(B:s (3OGQ UaGA(B,s, 2009)
(3eaghe GdLhOI GdTGedI ceONd dGOGQI GdLhOI , GdGOGQI GdGSJQGJjLjI (B: (3GdJNWjW h GdJfajP ddMUhd Ydi GdejRI GdJfGaSjI , KbGaI GdLhOI , QVGdA GdeSJgdcjf h GdGMJaGX Hge , Jecjf GdYGedjf , GdbjGOI h GdZjjQ, HfGA GdaQb h aQb GdYed , GdGJUGd GdaYGd , GdJOQjH h GdJYdje , GOGQI GdUQGY , GJNGP GdbQGQGJ h Md GdeTcdGJ , GdJMSjf GdeSJeQ h GdebGQHI GdeQLYjI , COhGJ GdLhOI GdTGedI(B.s
(3eQGLY U(B.315s
Keywords: (3GdEjRhs; (3GdLhOIs; (3GdLhOI `` GOGQIs; (3GdefXeGJs; (3VHW GdLhOIs